Education between Critique and Theology - Ḥotam, Yotam (Journal of ecumenical studies, 2021)
Recent debates in Israel highlight a resurfacing of the tensions between secular education and religion by assuming a clear separation between a critical attitude toward religion and the preparing of students for a life of religious obedience. Drawing on Theodor Adorno's discussion of education from the 1960's I wish to challenge this taken-for-granted assumption. I show how Adorno's famous educational appeal for "critical selfreflection" can be traced back to its theological sources. Specifically, I argue that, in Kierkegaard's theology of love, Adorno found a particular case for bringing together critique and theology that he then brought to bear on his educational position in which secular education and religion do not represent contradictory elements.